Literature study on the effectiveness of ethnoSTEAM on mathematics learning in elementary school based on baduy tribe’s craft art - Rahmawati, Rahmawati; Mastoah, Imas; Borda Rizalde, Marylyn (EduStream: Jurnal Pendidikan Dasar, 2025)
Mathematics learning in elementary schools is often considered abstract and less meaningful due to the lack of connection with real-life contexts. This study aims to examine the effectiveness of the application of the EthnoSTEAM approach based on Baduy tribal crafts in mathematics learning to improve concept understanding and foster love for local culture. This research uses the literature study method by analyzing accredited scientific sources, including journals from SINTA, Google Scholar, DOAJ, as well as books and related research reports. Data analysis was conducted through content analysis to examine the impact and challenges of implementing the EthnoSTEAM approach in primary education. The results show that the integration of Baduy craft arts such as Koja bags, weaving, batik, and pottery can help students understand mathematical concepts such as patterns, symmetry, flat shapes, perimeter, and volume more concretely. In addition, this approach encourages the development of critical thinking skills, creativity, and an appreciative attitude toward local culture. However, challenges include limited teacher training, lack of culture-based teaching materials, and lack of integrative support in the curriculum. In conclusion, the EthnoSTEAM approach based on Baduy craft art has the potential to enrich basic mathematics learning in a contextual and meaningful way.